Young families become mindful of their possibilities through the appreciation of their family life - Marie Poggenpoel; Frieda E. Jacobs; Chris P.H. Myburgh; Annie M. Temane (AOSIS, 2017)
Young families, as viewed through a multi-generational lens, provide the environment in which children can be nurtured and socialised. The purpose of the research is to explore and describe how the parents and grandparents of young families appreciate their family life. A qualitative, exploratory, descriptive and contextual multiple case study design was used to conduct the study. Purposive sampling methods were applied to select families according to the sampling criteria, each family representing an individual case study. Appreciative inquiry interviews were conducted with the young parents and available grandparents, during which the participants were asked four open-ended questions. Data collection was enriched by means of reflective letters to participants, collages created by the young parents, and the researcher's field notes and journal inscriptions. The data collected from each individual case study was analysed and then synthesised by means of a cross-case analysis. A cross-case validation report was compiled. The themes and categories that emerged from the data were discussed. The research study concluded that when young families embarked on a journey of discovering their strengths and potential in the larger family system, they creatively envision and discovered the possibilities to transform their destiny in a purposeful and constructive way.